The rs1051931 G>A Polymorphism in the PLA2G7 Gene Confers Resistance to Immunoglobulin Therapy in Kawasaki Disease in a Southern Chinese Population - Xueping Gu; Wenchun Lin; Yufen Xu; Di Che; Yaqian Tan; Zhaoliang Lu; Lei Pi; Lanyan Fu; Huazhong Zhou; Zhiyong Jiang; Xiaoqiong Gu; Xiaoqiong Gu (Frontiers in Pediatrics, 2020)
Background: Kawasaki disease (KD) is a common cardiovascular disease in infants and young children, with fever, rash, and conjunctivitis as the main clinical manifestations, which can lead to the occurrence of coronary aneurysms. Intravenous immunoglobulin (IVIG) is the preferred treatment for KD patients, but 10–20% of patients are resistant to IVIG. Lipoprotein-associated phospholipase A 2 (Lp-PLA2) is a potential therapeutic target for coronary atherosclerotic heart disease, and the polymorphism of Phospholipase A2 Group VII (PLA2G7) is closely related to the activity of Lp-PLA2, of which rs1051931 is the strongest. Therefore, the rs1051931 polymorphism may be a predictor of IVIG resistance in KD patients.Methods: A total of 760 KD cases, including 148 IVIG-resistant patients and 612 IVIG-responsive patients, were genotyped for rs1051931 in PLA2G7, we compared the effects of rs1051931 on IVIG treatment in KD patients by odds ratios (OR) and 95% confidence interval (CI).Results: The homozygous mutation AA may be a protective factor for IVIG resistance in KD patients (adjusted OR = 3.47, 95% CI = 1.14–10.57, P = 0.0284) and is more evident in patients with KD aged <60 months (adjusted OR = 3.68, 95% CI = 1.10–12.28, P = 0.0399).Conclusions: The PLA2G7 rs1051931 G>A polymorphism may be suitable as a biomarker for the diagnosis or prognosis of IVIG resistance in KD in a southern Chinese population.